2009
DOI: 10.1186/1477-7827-7-92
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Apolipoprotein D levels in human pregnancy and association with gestational weight gain

Abstract: BackgroundApolipoprotein D (ApoD) is a lipocalin involved in several processes including lipid transport, but its modulation during human pregnancy was never examined.MethodsWe investigated the changes in the levels of ApoD in the plasma of pregnant women at the two first trimesters of gestation and at delivery as well as in the placenta and in venous cord blood. These changes were studied in 151 women classified into 9 groups in relation to their prepregnancy body mass index (BMI) and gestational weight gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
2
17
0
1
Order By: Relevance
“…Interestingly, plasma apolipoprotein returned to baseline after birth more quickly in lactating women compared to those who were not breastfeeding. 40 In our study, colostral apolipoprotein D abundance was higher in women with GDM versus in women without GDM. Liao et al showed that apolipoprotein D levels were higher in colostrum relative to mature milk.…”
Section: Discussionsupporting
confidence: 45%
“…Interestingly, plasma apolipoprotein returned to baseline after birth more quickly in lactating women compared to those who were not breastfeeding. 40 In our study, colostral apolipoprotein D abundance was higher in women with GDM versus in women without GDM. Liao et al showed that apolipoprotein D levels were higher in colostrum relative to mature milk.…”
Section: Discussionsupporting
confidence: 45%
“…5053 Excess GWG has also been associated with alterations in metabolic markers in the maternal serum. 54 We recently demonstrated that the placental microbiome and the bacterial encoded metabolic pathways significantly vary in association with preterm birth. 8 Notably, these findings were independent of mode of delivery, which means that there were no differences in the placental microbiome of vaginal deliveries compared with cesarean deliveries.…”
Section: Commentmentioning
confidence: 99%
“…However, excess gestational weight gain (GWG) has also been associated with increased risk of preterm birth 5053 and alterations in metabolic markers. 54 Thus this begs the question, is it obesity or excess GWG that modulates the triad of inflammation, an altered placental microbiome, and spontaneous preterm birth?…”
mentioning
confidence: 99%
“…Neither the role nor the physiological ligands of ApoD have been clearly identified, but many studies suggest that it is a multifunctional protein binding many ligands (cholesterol, progesterone, pregnenolone, bilirubin and arachidonic acid), several of which are relevant in the reproductive tract [23,24]. The multifunctional role of ApoD is reflected by the fact that it is differentially expressed during cellular growth and differentiation, cancer, nervous system pathologies, inflammation and oxidative stress [10,25] and is inversely correlated with proliferation of fibroblasts in a tissue-specific manner [26].…”
Section: Commentsmentioning
confidence: 99%